2007
DOI: 10.1007/s10450-007-9059-8
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of the adsorption of metal ions to the surface of melanin particles

Abstract: We have re-examined the problem of the interaction of melanins with metal ions. Metal ions are normal constituents of the pigment, but in some cases they can be related to pathologies, mainly at the level of the skin (Cu 2+ and Fe 3+ ) and of the central nervous system (Fe 2+ and Mn 2+ ). Our approach has been based on the mechanisms of adsorption on the particle surface, by the use of theoretical adsorption isotherms and kinetic models. Although this analysis doesn't give detailed information on the specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…Fitting the data to several different models Bridelli and Crippa found the affinity order Zn 2+ < Cd 2+ < Cu 2+ [38], which is the same order as observed here. In their study with bovine eye melanin and synthetic eumelanin (produced by the L-dopa/tyrosinase method) Potts and Au found that Zn 2+ had lower binding efficiency than Pb 2+ and Cu 2+ , which had had similar binding efficiency (Cd 2+ was not tested) [36].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Fitting the data to several different models Bridelli and Crippa found the affinity order Zn 2+ < Cd 2+ < Cu 2+ [38], which is the same order as observed here. In their study with bovine eye melanin and synthetic eumelanin (produced by the L-dopa/tyrosinase method) Potts and Au found that Zn 2+ had lower binding efficiency than Pb 2+ and Cu 2+ , which had had similar binding efficiency (Cd 2+ was not tested) [36].…”
Section: Resultssupporting
confidence: 81%
“…The Langmuir affinity constants (Table 1) for the hair-extract- and synthetic-coated discs are within the range of values of affinity constants (10 3 to 10 7  M −1 ) obtained by a variety of methods for different metal ions with synthetic and natural melanin samples [7, 38]. Earlier reports have suggested that natural and synthetic eumelanin samples have a high affinity for Pb 2+ compared to other metal ions [35, 36], but affinity constants were not established in these studies, and until recently [18], current studies have generally not included lead.…”
Section: Resultsmentioning
confidence: 82%
“…darker individuals may suffer less in these habitats), both through direct and indirect effects of melanogenesis. First, melanin is composed of negatively charged free carboxyl, hydroxyl and amine functions known to bind metal ions in vitro (Larsson & Tj€ alve, 1978;Liu et al, 2004;Bridelli & Crippa, 2007). For this reason, metal chelation is suggested as one of the main biological functions of melanin (McGraw, 2003;Hong & Simon, 2007;Chatelain et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Because the property of melanin to bind metal ions may allow some body detoxification, we hypothesized that more melanic plumage may be selected in urban environments. Indeed, melanin is composed of several polymers with negatively charged free carboxyl, hydroxyl and amine functions which bind metal ions in vitro [14][15][16] explaining the relation found between some metals and melanic pigmentation [17]. Therefore, highly melanic birds could transfer more metals to their growing feathers during moult, thereby detoxifying their blood at a higher rate in comparison with less melanic individuals.…”
Section: Introductionmentioning
confidence: 99%